Daun Cempaka Kuning (Michelia champaca Linn) sebagai Kandidat Penghambat Enzim α-glukosidase secara In Silico - Amalia, Riyanti; Meiliana, Made Laksmi; Hamidu, La (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
Diabetes Mellitus (DM) is a chronic disease that occurs worldwide and continues to increase rapidly. The purpose of this study was to determine the activity and mechanism of action of the antioxidant compounds in cempaka kuning leaves as an antidiabetic using the in silico method. This study used 8 antioxidant compounds from cempaka kuning leaves, namely octadecadienoic acid, butanoic acid, oleic acid, camphorsulfonic acid, pimaric acid, phenol, andrographolide, and benzoic acid. The α-glucosidase enzymes used in this study were obtained from the Protein Data Bank website with the PDB ID codes 3A4A and 2QMJ. Ligand-macromolecule docking using AutoDockTools (ADT) and AutoDock Vina programs. The results showed that the antioxidant compounds in cempaka kuning leaves that had the lowest ΔGbind values were pimaric acid (-8.9 kcal/mol) and andrographolide (-8.6 kcal/mol) in PDB ID 3A4A. The docking results used PDB ID 2QMJ, the compound with the smallest ΔGbind was andrographolide (-7.4 kcal/mol). The results of visualization of the interaction of the ligand with the macromolecular amino acid residue PDB ID 3A4A showed that the residues Arg315, Arg442, and Tyr158 were found in the compound with the smallest ΔGbind. In the PDB ID 2QMJ macromolecule, Asp542 residue was found in all compounds with the smallest ΔGbind. Based on these results, the compounds pimaric acid and andrographolide have potential as antidiabetic drugs compared to other compounds with a mechanism of action of inhibiting the α-glucosidase enzyme.